The development of an instructional decisions test for secondary mathematics teachers - Baldeviso, Evelyn V. 1947- (Quezon City University of the Philippines Diliman, 1975)
An Instructional Decision Test which consists of fifteen exercises in an objective-strategy sequence was designed in this study to assess a teacher behavior-- that of identifying and selecting strategies best suited to attain specific objectives. This Instructional Decisions Test is recommended for methods courses in teacher training institutions as a basis of information on pre-service teacher performance.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines